2007
DOI: 10.1088/0960-1317/17/5/020
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible coatings for CMUTs in a harsh, aqueous environment

Abstract: The results of coating capacitive micromachined ultrasonic transducer (CMUT) arrays with two different biocompatible materials, parylene-c and polydimethylsiloxane (PDMS), are reported. These materials were characterized for use with CMUTs to enable direct contact transcutaneous and in vivo imaging. A passivation coating is required to provide electrical isolation to the active areas of the device and to protect it from a corrosive environment. It must also provide good mechanical characteristics to void imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…PDMS is a widely used material for fabricating lFDs (Gong and Wen 2009;Zhou et al 2010;Vullev et al 2006; Thomas et al 2010a). Despite its shortcomings, such as porosity (Li et al 2009;Mehta et al 2009;Chueh et al 2007;Shin et al 2003) and susceptibility to a broad range of organic solvents (Lee et al 2003), PDMS is biocompatible (Belanger and Marois 2001;Zhuang et al 2007) and allows for expedient and facile reproduction of features with nanometer precision that are essential for lFDs (Gates 2005;Cong and Pan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PDMS is a widely used material for fabricating lFDs (Gong and Wen 2009;Zhou et al 2010;Vullev et al 2006; Thomas et al 2010a). Despite its shortcomings, such as porosity (Li et al 2009;Mehta et al 2009;Chueh et al 2007;Shin et al 2003) and susceptibility to a broad range of organic solvents (Lee et al 2003), PDMS is biocompatible (Belanger and Marois 2001;Zhuang et al 2007) and allows for expedient and facile reproduction of features with nanometer precision that are essential for lFDs (Gates 2005;Cong and Pan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to apply a coating to a transducer: mold-transfer [2], spray coating, VDP [1], [3], and spin coating [3]. For CMUTs insulating layers are usually applied using mold-transfer to integrate a lens at the same time.…”
Section: Device Coating and Measurement Setupmentioning
confidence: 99%
“…Parylene C [1], [3], which gives good results and has the advantage of being cleanroom compatible, but is deposited using Vapor Deposition Polymerization (VDP). Silicon nitride has also been proposed due to cleanroom compatibility, however, the stress in the nitride highly affects the device performance [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, 12.7 μm -38.1 μm thick Parylene C filmstrips were immersed into solvent for six hours at most and the thickness measurements of the film layer were performed using an interference technique [12]. On the other hand, the efficiency of Parylene C film layer for the insulation of electronics was monitored only after exposure to moisture [5], [13]- [15]. Additionally, Kim et al [7] studied the effects of some chemicals (acetone, 2-propanol (IPA), AZ400K developer, MF319 developer, and buffered hydrofluoric acid (BHF)) on Parylene C bonding strength at different bonding temperatures and reported that prolonged exposure to chemicals decreases bonding strength significantly, especially for strong acids and bases.…”
Section: Introductionmentioning
confidence: 99%